Motherhood and Wage Discrimination, Evidences from NLSY 1982-2006, United States - Choi, Seul Ki (한국사회학, 2011)
This article explores the wage gap between mothers and non-mothers, which is called the motherhood wage penalty. Previous researches have focused on the loss of job experience due to motherhood as a key reason of the penalty. On the contrary, this paper focuses on discrimination against motherhood. Using data from the 1982-2006 National Longitudinal Study of Youth with residual analysis, I find that women are experiencing 2% of motherhood wage discrimination per child. It is roughly one-third of the gross motherhood wage penalty. I also find that sizes of the discrimination are different by the location in the occupational hierarchy. Managers/professionals are not suffering from wage discrimination. Whereas, manual workers are suffering from the discrimination, 3% per child. The 69% of the wage gap persists after controlling for productivity measures. Even among laborers and service workers, their penalties are 6% per child and more than 90% of wage gap is attributed to discriminatory factors. It implies that motherhood discrimination persists in spite of the declined gender wage discrimination, especially mothers who does not have authorities nor skills. The discrimination may just be modified or happen at a different boundary, from women vs. men, to mothers vs. non-mothers.